Role of Melatonin and Luzindole in Rat Mammary Cancer - YEGEN, BERRAK; UĞURLU, MUSTAFA ÜMİT (TAYLOR & FRANCIS INC, 2012)
Background: Recent studies have analyzed the efficacy of various agents in experimental chemoprevention trials. In our study, the effects of melatonin (Mel) and its antagonist Luzindole (Luz) on Heme oxygenase-1 (HO-1) in a NMU (N-methyl-N-nitrosourea)-induced rat mammary carcinoma model are investigated. We aim to demonstrate the relationship between Mel and HO-1. Methods: Spraque-Dawley rats were treated with NMU at age 55 days to induce mammary carcinoma. Forty-eight rats were divided into four groups consisting of: (a) physiological saline group (PSG); (b) control group, NMU is given; (c) Mel group (500 mu g daily); (d) Mel antagonist Luz group (0.25 mg/kg/day i.p.). The animals were sacrificed; their serum and tissues were sampled for histopathologic evaluation, markers of endocrine derangement (serum prolactin, estradiol, and progesterone levels), apoptotic changes, DNA fragmentation, markers of oxidative stress and HO-1 immune expression were measured. Results: Most tumors developed in the Luz group (42%), followed by the control group (33%), and the Mel group (17%). The tumor latency was longer in Mel-treated group (control and Luz at week 17, Mel at week 21). The maximum tumor volume was also smaller in Mel group when compared to control and Luz groups (p < .05). In Mel group estradiol, progesterone, and prolactin levels were decreased compared to control group (p < .001; p < .01; and p < .01) and levels of apoptotic activity and DNA fragmentation ratio increased. Conclusions: The increment of HO-1 expression with Mel is described; possible underlying mechanisms of these effects await further investigations.
Keywords: melatonin; luzindole; heme oxygenase-1; rat; mammary cancer; BREAST-CANCER; DIPHENYLAMINE REACTION; HEME OXYGENASE; GROWTH-HORMONE; EXPRESSION; PROLACTIN; INFLAMMATION; ESTROGENS